Impact of age on left ventricular geometry and diastolic function in elderly patients with treated hypertension. (3rd September 2017) - Toba, Ayumi; Kariya, Taro; Aoyama, Rie; Ishiyama, Taizo; Tsuboko, Yusuke; Takeda, Kazuhiro; Fujimoto, Hajime; Shimokado, Kentaro; Harada, Kazumasa
Abstract: Purpose: Left ventricular (LV) remodelling is observed in numerous patients with hypertension and is a principal cause of heart failure in elderly patients. The aim of this study was to determine the relationships between age and structural/functional LV remodelling observed in elderly hypertensive patients. Methods: A total of 557 elderly hypertensive patients (mean age: 74.0 ± 8.6 years) with preserved LV systolic function underwent echocardiography and 24-hour blood pressure (BP) measurement. Results: Overall, 41.1% of patients had LV hypertrophy, 77.9% had increased relative wall thickness (RWT) defined as RWT >0.42, and 31.8% had both. Logistic analysis of the entire study population showed that increased RWT was associated with both 24-hour systolic BP (odds ratio (OR) 1.38, 95% confidence interval (CI) 1.12 to 1.70) and age (OR 1.32, 95%CI 1.08 to 1.61), whereas increased RWT was associated only with age (OR 1.61, 95%CI 1.23 to 2.11) after excluding patients with LV hypertrophy. Univariate and multivariate linear regression analyses of all patients showed that LV diastolic echocardiographic parameters were consistently associated with age ( p ≤ .001) alone, even considering LV structural changes. Conclusions: Age was independently correlated with LV concentric/functional changes regardless of LV hypertrophy, suggesting that ageing is independently involved in the progression of LV remodelling.